A review of the families and genera of the hyperiidean amphipod superfamily Phronimoidea Bowman & Gruner, 1973 (Crustacea: Amphipoda: Hyperiidea) - Zeidler, Wolfgang (Zootaxa, 2004)
A taxonomic review of the families and genera of the hyperiidean amphipod superfamily Phronimoidea is presented. The systematic relationship of genera is examined in detail. The current genera seem to be well-defined taxonomic units but some such as Themisto and Hyperoche are in need of thorough taxonomic revision. The genera of the families Phronimidae, Phrosinidae and Dairellidae remain unaltered. Prior to this review, the family Hyperiidae comprised fourteen genera. These genera, except for Iulopis and Bougisia, are readily separated into two groups; 1) those withall pereonites separate, with coxae separate from pereonites, with mandibular palp in both sexes and in which both antennae of females consist of four articles, and 2) those with some anterior pereonites fused (up to the first five), with coxae fused with pereonites, with mandibular palp absent in females, and in which females have first antennae of two articles (2 3 in Hyperioides), and the second antennae are reduced to one article. The latter group comprises the genera Lestrigonus, Phronimopsis, Themistella, Hyperioides, Hyperietta, and Hyperionyx. It is proposed that this group be placed in a new family, Lestrigonidae fam. nov., derived from Lestrigonus, the oldest available generic name in the group. The remainder, which includes Hyperia, are retained in the family Hyperiidae. Iulopis and Bougisia do not fit into either of the above families, or with each other. Thus, two new families are proposed to accommodate them, Iulopididae fam. nov. and Bougisidae fam. nov. Keys are provided to families, genera and some species.